PERBANDINGAN OPAC PERPUSTAKAAN UNIVERSITAS INDONESIA DAN NATIONAL UNIVERSITY OF SINGAPORE LIBRARY - Thoriq Tri Prabowo (Perpustakaan Nasional RI, 2016)
OPAC as an information retrieval system is an important thing to meet the users and the information needed, so it need to be evaluated. This study is compare two OPAC (They are: UI and NUS Library). It is observed to understanding its features and performances, then analysis it quantitatively and qualitatively. The result of this study is aims to evaluate the two OPACs and to describes how the ideal OPAC for the users is.